A comparative study on the surface radiation characteristics of photovoltaic power plant in the Gobi desert. (January 2022) - Li, Zhenchao; Zhao, Yanyan; Luo, Yong; Yang, Liwei; Li, Peidu; Jin, Xiao; Jiang, Junxia; Liu, Rong; Gao, Xiaoqing
Abstract: In order to identify impacts of photovoltaic (PV) power plant on surface radiation, this paper conducted a comparative study on the surface radiation and surface albedo characteristics between the PV site and reference site in the Gobi area in Xinjiang, China in the summer of 2020. The results show that, the upward long-wave radiation at the PV site was significantly lower than that at the reference site in the night, while the two were basically the same during the daytime. The average surface albedo at the PV site (0.14) was 39.1% lower than that at the reference site (0.23). Net radiation was higher at the PV site than that at the reference site throughout the whole day. The average net radiation of the underlying surface at the PV site was 30.7% more than that at the reference site, 75% of which was contributed by lower upward shortwave radiation and 25% was due to nocturnal lower upward longwave radiation at the PV site. Highlights: Average surface albedo at photovoltaic power site decreases 39.1%. Upward long-wave radiation at photovoltaic power site decreases significantly. Average net radiation at photovoltaic power site increases 30.7%.